MENINGKATKAN MOTIVASI, KETERAMPILAN BERPIKIR KRITIS DAN KEWARGANEGARAAN EKOLOGIS MENGGUNAKAN MODEL PANDAI PADA SISWA SEKOLAH DASAR - Gina Maulida; Akhmad Riandy Agusta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Activities, motivation, critical thinking skills, ecological citizenship, and learning outcomes of fifth grade students of SDN Surgi Mufti 4 in Civics learning are still low. This study aims to describe student activities and examine the increase in motivation, critical thinking skills, ecological citizenship, and student learning outcomes through the application of the PANDAI learning model. Through 4 meetings of Classroom Action Research (PTK), there was an increase in student activity reaching 94%, learning motivation reaching 94%, critical thinking skills 97%, and ecological citizenship also 97%. Classical learning completeness reached 91% at meeting IV. This finding shows that the quality of the process and learning outcomes of students increased in Civics subjects with the application of the PANDAI learning model which proved to be effective.